Penentuan Kapasitas untuk Menetapkan Penyerahan Barang dan Perencanaan Produksi untuk Memenuhi Perjanjian Pengiriman Di CV. Cuellar Safe - Kencana, Erlangga Wisnu; Abdulrahim, Muslimin (Innovative: Journal Of Social Science Research, 2024)
Cuellar Safe is a company engaged in manufacturing products that make safes or safes with fire-resistant and demolition-resistant security systems to keep valuables safer. Lack of production capacity with a process that can be said to be quite long results in not achieving production targets and resulting in delays in delivery to customers. The type of research used in this research is descriptive and uses a quantitative approach. Through descriptive research, researchers can provide an overview of the object being researched using data obtained through observation and analysis in order to identify relationships between variables. The results of this research are for forecasting in meeting production demand at CV. Cuellar Safe, after conducting research by the author, obtained forecasting results for the next 6 months with results of 29.3333, 33.3333, 35.6667, 37.3333, 36.3333 and 34.3333. Observation and calculation of Charity Box 5658, (94 Hours), BPKB Filing Cabinet 5842 (97), ZIB T.54 4687 (78 Hours), Perfect Size III 5754 (96 Hours). to meet production capacity at CV. Cuellar Safe researchers used linear programming as a basis for calculations with the Lingo platform and found the results X1 = 142, X2 = 53, X3 = 50,667, To determine suppliers to fulfill demand for raw materials at CV. Cuellar Safe using the AHP method and it was found that supplier B's results were very better than the other two suppliers. The suggestion that might be a reference for companies is to increase production capacity by increasing working hours. This can be done by imposing overtime or adding work shifts. Companies must pay attention to labor SOPs both in delivery, stock and production processes so that there are no delays. production and order delays. Companies must know the capacity the company has so that there are no delays in orders.